Simulation Research of Potential Contrast Agents for X-Ray Fluorescence CT with Photon Counting Detectors - Yan, Luo; Peng, Feng; Ruge, Zhao; Yi, Zhang; Kang, An; Peng, He; Shenghao, Yan; Xiansheng, Zhao (Frontiers in Physics, 2021)
XFCT is a novel method for the early cancer detection. Increasing concentration of contrast agents and incident X-rays’ energy were used to improve detecting accuracy, which greatly increased the prevalence of contrast-induced nephropathy. Therefore, this research explores the adaptive contrast agents and uses Geant4 to simulate the imaging conditions of Pt, Bi, Gd, Ru, and Au for searching the lowest detectable concentration based on the fast multi-pinhole collimated XFCT (fmpc-XFCT) imaging system and low incident energy. Several imaging parameters including pinhole radius (0.7, 0.8, and 1 mm) were adjusted, and the optimized EM-TV algorithm was used to reconstruct XFCT images. It is found that Bi element is superior to other metal elements in terms of the contrast-to-noise ratio (CNR) and fluorescence efficiency, and the lowest concentration that can be detected is 0.12% with optimal parameters.